Content Analysis of the articles in Journal of Linguistic and Rhetorical Studies of Semnan University (2010 - 2023) - Hossein Moradi Moghadam (مطالعات زبانی و بلاغی)
The Journal of Linguistic and Rhetorical Studies is one of the core journals in its Journal of Linguistic and Rhetorical Studies, having reached the first quarter and received the A rank, is one of the core humanities journals of Semnan University. Due to its significant status, the present research was conducted with the aim of analyzing the content of the articles of published in this Journal spanning the years 2010/1389 to 2023/1402. This research was done using the content analysis method for the statistical population of the 370 scientific articles published by Journal of Linguistic and Rhetorical Studies of Semnan University from 2010 to 2023. Sampling was not used in this research and the research population was investigated by census. By examining each article, necessary data were collected and analyzed using Excel software. The findings of the research showed that from 2010 to 2023, 370 articles were published in Journal of Language and Rhetoric Studies of Semnan University. Most of the articles were written by male authors (65% of the articles), with the scientific rank of assistant professor (30% of the articles), and the organizational affiliation of most of the articles belonged to Semnan University (10% of the articles). Concerning the variety of the disciplines, the fields of Persian language and literature (75 percent), general linguistics (7 percent), and Arabic language and literature (5 percent) showed the highest rate of publication. In the review and analysis of the journal articles, 1600 topics were identified with open code, out of which about 500 more frequent topics were selected in about 20 main topics. The first to third ranks of the main topics were dedicated to poetry and poets (9 percent), rhetoric (7.9 percent), and style and stylistics (6.3 percent). These were followed by metaphor, language and linguistics, sonnets and sonnets sequences, analysis, image and visualization. The remaining ten topics of the 370 articles were related to literary devices, literary elements, language structure, literature, story, simile, music, aesthetics, literary layers, grammar, and other fields. In the process of internationalization of publications, geographical distribution of authors is an important indicator. Since the review and analysis of the articles of Journal of Linguistic and Rhetorical Studies showed that the pattern of publishing articles was based on domestic authors, planning is deemed necessary to elevate the geographical distribution of authors at the international level.